KORELASI DIAMETER SELUBUNG NERVUS OPTIK DAN MARSHALL CT SCORE DENGAN SKALA KOMA GLASGOW PADA CEDERA KEPALA - Rani Maria Yogipranata; Hermina Sukmani (PERDOSNI, 2018)
CORRELATION BETWEEN OPTIC NERVE SHEATH DIAMETER AND MARSHALL CT SCORE WITH GLASGOW COMA SCALE IN TRAUMATIC BRAIN INJURYABSTRACTIntroduction: In traumatic brain injury (TBI), non-contrast brain CT scan is able to detect an increase in intracranial pressure, which is crucial in patient’s management. Optic nerve sheath diameter’s (ONSD) measurement is a new method that is expected to assess an increase in intracranial pressure noninvasively. Marshall CT score is a valid instrument, a de facto standard to classify head injury patient which correlates with an increased intracranial pressure.Aims: To see the correlation between ONSD and Marshall CT score with Glasgow Coma Scale (GCS).Methods: This was a retrospective, analytic observational with cross-sectional research’s design taken from the patients’ medical record admitted in Dr. Kariadi Hospital, Semarang, between March-August 2017. Measurement of ONSD and Marshall CT score were done by a radiologist. Rank Spearman’s were used to assess the correlation between variables.Results: There were 34 subjects, the majority were man (67,6%), with highest incidents in less than 30 years age (41,2%) and mostly caused by accident (76,4%). Statistical analysis showed a moderate negative degree correlation between ONSD and Marshall CT score with GCS.Discussion: Enlargement of ONSD and higher Marshall CT score were correlated negatively related with the GCSin TBI patients with increased intracranial pressure.Keywords: Glasgow Coma Scale, Marshall CT score, optic nerve sheath diameter’s, traumatic brain injuryABSTRAK Pendahuluan: Pada cedera kepala atau traumatic brain injury (TBI), penggunaan CT scan kepala tanpa kontras dapat mendeteksi tanda-tanda peningkatan tekanan intrakranial (TIK), yang penting bagi tata laksana pasien. Sementara pengukuran diameter optic nerve sheath yang disebut optic nerve sheath diameter (ONSD) merupakan metode baru yang diharapkan dapat menilai peningkatan tekanan intrakranial secara non-invasif. Marshall CT score merupakan instrumen valid dan menjadi standar de facto dalam mengklasifikasikan pasien cedera kepala yang berkorelasi dengan peningkatan TIK.Tujuan: Untuk melihat adanya korelasi antara diameter N. Optikus dan Marshall CT score dengan Skala KomaGlasgow (Glasgow Coma Scale/GCS).Metode: Penelitian analitik observasional retrospektif secara potong lintang dari data rekam medis pasien cedera kepala dewasa yang dirawat di RSUP Prof. Dr. Kariadi, Semarang, pada bulan Maret-Agustus 2017. Selanjutnya kesemua subjek dilakukan pengukuran ONSD pada kedua mata serta penilaian Marshall CT score oleh seorang spesialis radiologi. Dilakukan uji korelasi Rank Spearman’s untuk menilai ketiga parameter tersebut.Hasil: Terdapat 34 subjek yang terutama laki-laki (67,6%) dengan usia terbanyak <30 tahun (41,2%) dan penyebab terbanyak adalah kecelakaan (76,4%). Didapatkan korelasi negatif derajat sedang antara ONSD dan Marshall CT score dengan GCS.Diskusi: Peningkatan diameter optic nerve sheath dan Marshall CT score berkorelasi dengan penurunan skor GCSpada pasien cedera kepala yang mengalami peningkatan TIK.Kata kunci: Cedera kepala, diameter optic nerve sheath, Marshall CT score, Skala Koma Glasgow